Comparing Heterotopic Ossification in Two Cervical Disc Prostheses. Issue 19 (1st October 2020) - Yang, Xiaoyu; Donk, Roland; Bartels, Ronald H.M.A.; Arts, Mark P.; Depreitere, Bart; Vleggeert-Lankamp, Carmen L.A.
Abstract : Study Design: Retrospective analysis using data from randomized clinical trials. Objective: To compare the occurrence of heterotopic ossification (HO) between two cervical disc prostheses. Clinical outcome and range of motion (ROM) were also evaluated. Summary of Background Data: Cervical arthroplasty was reported to be able to maintain the segmental ROM. However, controversy exists since the difference of the occurrence of HO concerning cervical prosthesis is still huge. Methods: Patients who underwent anterior cervical discectomy with arthroplasty for a cervical radiculopathy due to a herniated disc from the The Netherlands Cervical Kinematics (NECK) trial (activC; metal endplates with a polyethylene inlay and a keel for primary stability) and the PROCON trial (Bryan; metal-on-polymer with titanium coated endplates without a keel) were analyzed for HO at 12 and 24 months postoperatively. HO was scored according to the McAfee–Mehren classification. Segmental ROM was defined by a custom developed image analysis tool, and global cervical ROM was measured by Cobb's angle. Clinical outcome was evaluated by means of the neck disability index (NDI) as well as physical-component summary (PCS) and mental-component summary (MCS). Results: At 2-year follow-up, the occurrence of HO was 68% in patients treated with the activC prosthesis (severe HO 55%), which was comparable with 85% ( P  = 0.12) in patients with the Bryan disc (severe HO 44%; P  = 0.43). The HO progression was similar between groups. Clinically, the patients had comparable NDI, PCS, and MCS at 2-year follow-up, and comparable improvement of clinical outcomes. The global ROM in the Bryan group (56.4 ± 10.8°) was significantly higher than in the activC group (49.5 ± 14.0, P  = 0.044) at 2-year follow-up. Conclusion: In comparison of two cervical disc prostheses the development of HO is independent on their architecture. Although global ROM was higher in the Bryan prosthesis group, this difference was not deemed clinically important, particularly because the clinical condition of patients with and without severe HO was comparable. Level of Evidence: 2 Abstract : It is a controversial issue that the difference of the occurrence of heterotopic ossification (HO) concerning cervical prosthesis is still huge. In this study, in the two cervical disc prostheses the development of HO is independent on their architecture.